EVALUASI OUTCOME KEBIJAKAN PUBLIK (Studi Kasus: Evaluasi Outcome Kebijakan UN SD di Kota Madya Jakarta Pusat) - Dikson Silitonga (Lembaga Riset dan Pengabdian Masyarakat Institut Bisnis Nusantara, 2018)
In general, this research is aimed at evaluating to what extent the effectiveness of implementation of National Exam policy in mapping and increasing the quality of primary education in Indonesia. By using the Stake’s Countenance evaluation model, this research uses a qualitative and descriptive statistic (simple quantitative) approach with the techniques of data collection through a library study as secondary data sources, deep interviews and observation as primary data sources.This research is intended to evaluate the outcome phase. On the outcome phase, it seems that the quality of education is still low and unprevalent.